2013
DOI: 10.1080/17458080.2011.597441
|View full text |Cite|
|
Sign up to set email alerts
|

Nano-appended transdermal gel of Tenoxicam via ultradeformable drug carrier system

Abstract: Tenoxicam is one of the potent non-steroidal anti-inflammatory drugs (NSAIDs), which is used clinically in the treatment of rheumatoid arthritis. Like other NSAIDs, Tenoxicam also suffers from the drawback of being associated with gastrointestinal side effects. Further, transdermal penetration of this drug is very poor, which circumvents the use of transdermal route. The main objective of this study is to exploit the concept of ultradeformable vesicles to increase the transport of Tenoxicam through transdermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…TX adverse effects' profile is comparable to that of other NSAIDs as it mainly affects the GI tract initiating epigastric pain, indigestion, dyspepsia, vomiting, and GI ulceration (Gonzalez and Todd, 1987). Further, it has been reported that transdermal penetration of TX is very poor limiting its use transdermally (Gwak and Chun 2001;Negi et al, 2013). Accordingly, the aim of the present work was to investigate the ability of bilosomes to increase the transdermal transport of TX, thereby, avoid unnecessary GI side effects associated with oral administration.…”
Section: Introductionmentioning
confidence: 97%
“…TX adverse effects' profile is comparable to that of other NSAIDs as it mainly affects the GI tract initiating epigastric pain, indigestion, dyspepsia, vomiting, and GI ulceration (Gonzalez and Todd, 1987). Further, it has been reported that transdermal penetration of TX is very poor limiting its use transdermally (Gwak and Chun 2001;Negi et al, 2013). Accordingly, the aim of the present work was to investigate the ability of bilosomes to increase the transdermal transport of TX, thereby, avoid unnecessary GI side effects associated with oral administration.…”
Section: Introductionmentioning
confidence: 97%
“…Although, some particles were found to be clusters but mostly was in uniform dispersion and uniform distribution in respect to overall formulation [21]. Average Particle size and Zeta potential: Particle size of SSD loaded nanogel were subjected initially through Zeta sizer which result was revealed that the size of the particle was affected by concentration of noveon polycarbophil AA1 and homogenization time [23]. Although particle size of the formulation FG-5 was found to be within the range i.e.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…Injectable formulations like in situ-forming microparticles, showed promising results as TNX delivery vehicles in terms of anti-inflammatory and antioxidant activity for rheumatoid arthritis [ 29 ]. Moreover, TNX has been encapsulated into delivery systems such as microemulsion-based formulations [ 30 ], proniosomes [ 31 ] and ultradeformable vesicles based on surfactant molecules [ 32 ], for transdermal and topical applications.…”
Section: Introductionmentioning
confidence: 99%